Policy, Practicalities, and PACE s. 24: The Subsuming of the Necessity Criteria in Arrest Decision Making by Frontline Police Officers. (16th April 2018) - Pearson, Geoff; Rowe, Mike; Turner, Liz
Abstract : PACE, as amended by the Serious Organised Crime and Police Act 2005, establishes a complex framework of factors that police officers must consider during arrest decision making. Officers must possess a reason to arrest, it must be necessary to arrest for that reason, and they must give at least a 'cursory consideration' to alternatives. Based on a four‐year ethnographic study of frontline officers from two forces in Northern England, we argue that the 2005 reforms have not achieved their aims. The new regime tasks officers with undertaking a complex legal assessment prior to arrest, but officers are often confused about the necessity criteria which, moreover, is typically a minor consideration in contrast to demanding practical and policy pressures. This means that unlawful and non‐human‐rights‐compliant arrests continue to be regularly made and, equally significantly, many suspects are escaping the criminal justice system because officers are not considering arrest alternatives.